The IMIA WGI database on health and medical informatics programs and courses: A Call for Participation - Haux, Reinhold; Frank, Jürgen; Knaup-Gregori, Petra (Methods of information in medicine, 1997)
Working Group 1 on health and medical informatics education of the International Medical Informatics Association (IMIA) has established a WWW site (http://ix.urz.uni-heidelberg.de/ ~ d16) to provide up-to-date information about its work. The core of the site is an underlying database providing information on health and medical informatics (HMI) programs and courses worldwide. To be able to have a database of high quality and value we encourage all teachers and institutions to submit information about courses and programs on HMI education offered and to set pointers to their own WWW sites. In addition, a mailing list was installed to facilitate communication between all persons interested in HMI education. For subscription a message has to be sent to “listservlistserv.net”. The body of the message should read “SUBSCRIBE IMIA-WG1”. Messages to the IMIAWG1 list have to be sent to “imia-wg1@urzinfo.urz.uni-heidelberg.de”.